The Role of Islamic Autonomous Motivation in Sustainable Employee Innovative Behavior - Aisyah, Syahrainy; Sulistyo, Heru; Cahyono, Budhi (Journal of Posthumanism, 2025)
The batik industry is one of the mainstay sectors in the implementation of Making Indonesia 4.0. Batik is part of the textile and fashion industry which is a cultural identity of the nation that emphasizes the creativity, ability and innovation of each worker so that they are able to create innovative and distinctive products . Sustainable employee innovative behavior has an important influence on the development of organizational innovation. Therefore, it is important to identify the antecedents of sustainable employee innovative behavior. This article discusses a new concept, namely Islamic Autonomous Motivation . This concept is based on the absence of restrictions on freedom in determining choices and the freedom to act which is a dilemma of employee autonomous motivation. This study took data through the distribution of questionnaires with respondents are employees of small and medium batik industry. The results of this study indicate that Islamic Autonomous Motivation mediates the relationship between Leader Autonomy Support (LAS) and Sustainable Employee Innovative Behavior (SEIB). Leader support has an important influence in increasing employee autonomy motivation which will also affect the increase in sustainable employee innovative behavior.